College choice, selection, and allocation mechanisms: A structural empirical analysis - José Raimundo de Araújo Carvalho Júnior; Thierry Magnac; Qizhou Xiong (Quantitative Economics, 2019)
We use rich microeconomic data on performance and choices of students at college entry to analyze interactions between the selection mechanism, eliciting college preferences through exams, and the allocation mechanism. We set up a framework in which success probabilities and student preferences are shown to be identified from data on their choices and their exam grades under exclusion restrictions and support conditions. The counterfactuals we consider balance the severity of congestion and the quality of the match between schools and students. Moving to deferred acceptance or inverting the timing of choices and exams are shown to increase welfare. Redistribution among students and among schools is also sizeable in all counterfactual experiments.
Keywords: C57; D47; I21; 330; Education; two-sided matching; school allocation mechanism; policy evaluation